2006
DOI: 10.1007/s00125-006-0275-7
|View full text |Cite
|
Sign up to set email alerts
|

Estimating glomerular filtration rate in diabetes: a comparison of cystatin-C- and creatinine-based methods

Abstract: Aims/hypothesis: We compared the predictive performance of a GFR based on serum cystatin C levels with commonly used creatinine-based methods in subjects with diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
130
6
7

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 152 publications
(148 citation statements)
references
References 10 publications
5
130
6
7
Order By: Relevance
“…In a recent comparison of rates of decline of GFR in type 1 diabetes at our centre, serial estimates of GFR decline by creatinine-based methods in patients with an initial isotopically measured GFR of 106±2.6 ml min −1 1.73 m −2 underestimated the GFR gradient measured isotopically by over 50% during a follow-up of 10 years [73]. In contrast, we and others have shown that cystatin Cbased methods for estimating GFR accurately reflect reference GFR measurements in the normal to high range [73][74][75][76].…”
Section: Resolution Of Hyperfiltration In Clinical Trialsmentioning
confidence: 56%
“…In a recent comparison of rates of decline of GFR in type 1 diabetes at our centre, serial estimates of GFR decline by creatinine-based methods in patients with an initial isotopically measured GFR of 106±2.6 ml min −1 1.73 m −2 underestimated the GFR gradient measured isotopically by over 50% during a follow-up of 10 years [73]. In contrast, we and others have shown that cystatin Cbased methods for estimating GFR accurately reflect reference GFR measurements in the normal to high range [73][74][75][76].…”
Section: Resolution Of Hyperfiltration In Clinical Trialsmentioning
confidence: 56%
“…In contrast to the MDRD equation, which was calculated from a large population in a multicenter study, CysC-based equations were created and validated in smaller samples using different gold standard measurements for GFR. Table 3 highlights some CysCbased equations for adults (29,45,(51)(52)(53)(54)(55)(56).…”
Section: Equations Estimating Gfr Based On Cystatin Cmentioning
confidence: 99%
“…The vast majority, when comparing bias, precision, accuracy, and correlation, found CysC-based equations to be superior to creatinine-based equations as estimates of GFR (45,52,53), while some reported no difference in the performance of CysC-and creatinine-based equations (29,54). Recently, in order to improve the estimated kidney function, estimated GFR equations were developed, which incorporate both SCr and CysC.…”
Section: Equations Estimating Gfr Based On Cystatin Cmentioning
confidence: 99%
“…El-Shafey i saradnici [19] su pokazali da je oblast koju pokriva ROC kriva bila najviša za jednačinu JGF iz cistatina C u odnosu na jednačinu iz kreatinina i 24-časovni kreatinin. Slične rezultate pokazao je MacIsaac sa saradnicima [20]. Oni su kod oboljelih od DM tipa 2 upoređivali jednačine JGF izračunate iz serumskog cistatina C i kreatinina, te dobijene vrijednosti JGF upoređivali sa referentnom metodom, odnosno klirensom dietilen-triaminopentaacidna kiselina.…”
Section: Diskusijaunclassified